The Use of Technology in Teaching and Learning English through E-Learning for Students College - Mulyati, Sri (PPSDP International Journal of Education, 2023)
The purpose of the study is to give information to the teachers on teaching needs using technology, especially in the classroom. For now, we are faced with the Pandemic Covid-19 and teachers continue to be demanded to be more careful in choosing the right technology when teaching online. E-learning is one of the digital platforms for learning in the digital era. This type of research is the methods library research. This article is literature-based in which the data and information were gathered from books, internet postings, journals, social media, etc. Technology includes the use of materials, tools, techniques, and sources of power to make life easier. In education, Technology is really able to improve the teaching and learning process, especially in teaching English during the pandemic.